Evaluating Ihsan Behavior, Work Engagement, Job Performance With Employee Well-Being As A Mediator - Ryan Basith Fasih Khan; Aisyah Nur Rahmadini; Dena Maulidi Hannana (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Syekh Wasil Kediri, 2024)
This study examines the relationship between organizational Ihsan Behavior, Work Engagement, and Job Performance, with Employee Well-Being as a mediator. The cross-sectional study investigates organizational dynamics under constant change. According to the research, Ihsan Behavior significantly affects employee work engagement. This strengthens our understanding of Ihsan Behavior's impact on employee work performance and the need for organizational practices that support it. The study also helps explain the mediating role of Employee Well-Being in Ihsan Behavior and Work Engagement. These insights aid in analyzing employee engagement elements. This research shows that emphasizing employee well-being and fostering strong interpersonal interactions among colleagues is crucial for creating a workplace culture that supports employee engagement and long-term organizational performance. Firms can use this research's methodology to achieve their business goals and cultivate a workplace culture committed to their success.